"A Gay Agenda": Troubling Compulsory Heterosexuality in a South African University Classroom. (July 2021) - Francis, Dennis A.
Not only does teaching about gender and sexuality diversity lead to some very interesting and often emotionally evocative, pedagogical exchanges; it can also create challenging issues for teachers and students alike. This article focuses on what happens when a module that addresses compulsory heterosexuality and schooling is broached in an undergraduate sociology class. More importantly, it offers an analysis of the critical incidents and tensions that pay specific attention to how power, knowledge, and emotion feature in teaching and learning. Using antioppressive and affect theories, this article offers an analysis of how we might understand pedagogical practice, especially as it relates to addressing the power of normative heterosexuality in a university classroom. With reflections emerging from the module, I argue for more sociological theorization and analysis of the role of affect in pedagogies that seek to advance liberatory teaching and learning in the area of anti-heterosexism education.